Enhancing Imagination Through Finger Painting Activities in 5-6 Year Olds - Rohali, Alia; Sitorus, Masganti (Universitas Islam negeri Mahmud Yunus Batusangkar, 2025)
The development of imagination in early childhood is crucial for supporting creativity and cognitive abilities. This study aims to enhance the imagination of children aged 5-6 years through the finger painting activities using Classroom Action Research (CAR) with two cycles, involving 15 children aged 4-6 years as subjects. Initial observations revealed that most children were in the